Knowledge Management for Business - Mercier-Laurent, Eunika (Zarządzanie wiedzą w biznesie, 2010)
Knowledge Management was introduced in companies in the early 1990s as a management method. In the same time knowledge was managed in the various knowledgebased systems, such as decision support, diagnostic, optimisation, scheduling, process control and others. Artificial Intelligence method and tools have been also used in finance, prediction, insurance and banking services. This paper presents the current trends in Knowledge Management, including web 2.0, and describes economic changes and their consequences on the way of doing business through Collaborative Innovation Systems. Future KM has to help all internal and external knowledge cultivators1 to be successful in capturing ideas and transforming them into values. KM is also considered as management method for the Knowledge Economy. We give some precisions on the components of the Kflow to effectively assist the Collaborative Innovation Systems.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 133, s. 79-88
Keywords: knowledge management; artificial intelligence; innovation